A Delphi Study for the Development of an Infant Skin Breakdown Risk Assessment Tool. (April 2015) - Vance, Deborah A.; Demel, Sharon; Kirksey, Kenn; Moynihan, Marcie; Hollis, Karen; Dowling, Donna
<x xml:space="preserve">Abstract</x> Background: Infants, especially those born prematurely, are at increased risk for skin breakdown because of the immaturity and fragility of their skin. Following a review of existing skin risk assessment tools, we concluded that none provided valid, clear, and concise assessment criteria and direction for treatment interventions specifically for use with neonates. Purpose: To examine the risk factors of skin breakdown in infants using the knowledge of interprofessional providers who routinely care for infants. Combined with scientific knowledge, this could potentially result in a valid, reliable, and useable skin risk assessment tool. Methods: Using an online survey tool, 2 rounds of the Delphi technique were conducted with interprofessional providers who routinely care for infants. During round 1, participants were asked, "What do you perceive as risk factors for skin breakdown in neonates?" Responses for round 1 were categorized into themes. In round 2, respondents were asked to rank the importance of these themes using a 5-point Likert scale. Results: These data resulted in the creation of the Seton Infant Skin Risk Assessment Tool, currently being further validated through a retrospective chart review. Responses were categorized into themes, including the use of medical devices, postmenstrual age/birth weight, activity/movement, comorbidities, skin integrity/tolerance, moisture/chemicals, and nutrition/hydration. Implications for Practice: All infants in neonatal intensive care units (NICUs) are at risk of skin breakdown. Matching a risk assessment tool with routine skin assessment and a risk-related care plan could result in a reduction of skin breakdown in these infants. Implications for Research: A retrospective study of infants in 2 Level III NICUs and 1 Level IV NICU is being finalized, which will result in an infant skin risk assessment tool as well as a tool describing methods to minimize each risk factor. Further research will be needed to test the interrater reliability and validity of the tool and increase knowledge of skin breakdown prevention practices.